Factors associated with participation in colorectal cancer screening: A population‐based study of 7200 individuals. (17th November 2020) - Huang, Junjie; Choi, Peter; Pang, Tiffany W. Y.; Chen, Xiao; Wang, Jingxuan; Ding, Hanyue; Jin, Yinzi; Zheng, Zhi‐Jie; Wong, Martin C. S.
Abstract: Objective: This study aimed to evaluate how the knowledge and perception towards colorectal cancer (CRC) screening had been changed in a large population, and identified factors associated with its participation based on factors pertinent to the Health Belief Model (HBM). Methods: Data from 3600 screening participants and 3600 non‐participants were collected through a telephone survey via simple random sampling of telephone numbers in a territory‐wide directory from December 2016 to November 2018. Sociodemographic factors; the enabling factors of screening as well as the barriers of screening were collected. The changes in these factors were evaluated by Pearson's chi‐square trend test. A logistic regression model was constructed to identify the association between the above factors and CRC screening participation. Results: The knowledge level (67.9% to 85.4%, p < 0.001), perceived severity of having CRC (37.7%–42.8%, p < 0.01), perceived benefits of screening (54.9%–72.1%, p < 0.001), and reductions in barriers (14.1%–5.1%, p < 0.001) of CRC screening significantly improved among the non‐users. Subjects with older age (adjusted odds ratio (AOR): 2.01, p < 0.001), higher knowledge level of screening methods (AOR: 6.68, p < 0.001), greater perceived severity (AOR: 2.04, p < 0.001) and coverage of insurance (AOR: 1.22, p < 0.01) were more likely to participate. In contrast, more affluent subjects (AOR: 0.69, p < 0.001), female individuals (AOR: 0.63, p < 0.001), higher level of perceived psychological (AOR: 0.54, p < 0.001) and access barriers (AOR: 0.55, p < 0.001) were associated with poorer participation. Conclusion: These findings demonstrated a substantial increase in the enabling factors of CRC screening, including knowledge, perceived severity and perceived benefits. The study also identified the target groups such as younger individuals, females and more affluent people among whom more intensive educational initiatives are needed to enhance their participation.